Measuring Theory of Mind: a preliminary analysis of a novel linguistically simple and tablet-based measure for children - Baumeister, Franziska; Wolfer, Pauline; Sahbaz, Sümeyra; Rudelli, Nicola; Capallera, Marine; Daum, Moritz M.; Samson, Andrea C.; Corrigan, Grace; Naigles, Letitia; Durrleman, Stephanie (Frontiers in Developmental Psychology, 2024)
This study introduces a novel linguistically simple, tablet-based, behavioral Theory of Mind (ToM) measure, designed for neurotypical (NT) and autistic children aged four to ten years. A synthesis of five comprehensive reviews of existing ToM measures revealed significant gaps in their designs; the weaknesses include a mismatch between the operational and conceptual definition of ToM, high verbal demands in most measures, materials that are minimally interesting for children, and often a lack of psychometric evaluations. These findings call into question the suitability of most of the currently available ToM measures used in children, both with and without developmental disorders, such as children with autism spectrum disorder (ASD). For example, the assessment of ToM in children with ASD may require reduced reliance on complex language or social interaction that can be part of the diagnostic criteria of the condition. This newly designed ToM measure, developed in line with the "Standards for Educational and Psychological Testing" of the American Educational Research Association, is linguistically simple, tablet-based, suitable for children with ASD, and is available in English, German, French, Italian, and Spanish. With a sample of 234 participants, including 152 NT children and 82 children with ASD between four and ten years of age, the new ToM measure's psychometric properties were preliminarily evaluated. Descriptive statistics, measures of internal consistency, inter-item correlation, and validity checks were conducted in both groups. Further inspections of the measure's scale-and item-level characteristics were conducted with the help of exploratory factor analyses (EFA), and item response theory (IRT) within the NT children's group. These preliminary evaluations suggest that the newly developed ToM measure possesses good psychometric properties and is both accessible and engaging for children. Further investigation with a larger group of participants is necessary to reinforce these initial results. This will allow item-and scale-level assessments within a wider range of autistic children. For this purpose, the task will be made freely available to the scientific community.2 For a detailed overview of the results of the pilot study with 40 NT adults, please see the Supplementary material.